Contingent Fees and Tax Compliance - Phillips, John; Sansing, Richard C. (The Accounting Review, 1998)
[This paper examines the effects of banning contingent fees for tax return preparation services. The paper presents a principal-agent model in which a taxpayer contracts with a tax practitioner to attempt to resolve tax law uncertainty. The optimal contract provides incentives for the practitioner to do research and to choose the tax return reporting position that the taxpayer prefers. Analysis of the model shows that banning contingent fees raises the expected fee of the practitioner. The amount of this increase is increasing in the quality of the practitioner. Conventional wisdom holds that contingent fee arrangements will lead to an increase in tax undercompliance. In contrast, we find that undercompliance decreases when contingent fees are allowed.]